2014
DOI: 10.1175/jas-d-13-0190.1
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Study of Tropical Cyclones in Rotating Radiative–Convective Equilibrium with Column Physics and Resolution of a 25-km GCM

Abstract: Rotating radiative–convective equilibrium is studied by extracting the column physics of a mesoscale-resolution global atmospheric model that simulates realistic hurricane frequency statistics and then coupling it to rotating hydrostatic dynamics in doubly periodic domains. The parameter study helps in understanding the tropical cyclones simulated in the global model and also provides a reference point for analogous studies with cloud-resolving models. The authors first examine the sensitivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 18 publications
10
68
0
Order By: Relevance
“…As found in the spherical geometry simulations, PI captures the variation in maximum surface wind speed but underestimates the minimum simulated SLP in the rotating RCE simulations (see Zhou et al [] for further discussion). In both cases, we find that the PI calculations are sensitive to the assumption that the surface relative humidity in the TC eyewall, which is nearly saturated in the simulations, is equal to the surface relative humidity of the environment.…”
Section: Simulation Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…As found in the spherical geometry simulations, PI captures the variation in maximum surface wind speed but underestimates the minimum simulated SLP in the rotating RCE simulations (see Zhou et al [] for further discussion). In both cases, we find that the PI calculations are sensitive to the assumption that the surface relative humidity in the TC eyewall, which is nearly saturated in the simulations, is equal to the surface relative humidity of the environment.…”
Section: Simulation Resultsmentioning
confidence: 74%
“…The rotating RCE, f ‐plane simulations also have a decreasing number of TCs as the SST is increased [ Zhou et al , ]. The rate of decrease is ∼12% K −1 in the rotating RCE simulations (dotted line in Figure a), which is an ∼50% higher sensitivity to SST than found in spherical geometry.…”
Section: Simulation Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, Zhou et al . [] explored the dependence of the equilibrium state upon domain size using a model similar to Held and Zhao []. They found that as domain size increases, the equilibrium evolves through four regimes: a single tropical depression, an intermittent tropical cyclone with widely varying intensity, a single sustained storm, and finally multiple storms.…”
Section: Introductionmentioning
confidence: 99%
“…HiRAM is developed based on AM2 (GAMDT, 2004) with increased resolutions and simplified parameterizations for moist convection and stratiform cloudiness. It has thus been used to examine the response of TC activity to climate change in both comprehensive and idealized simulations (Ballinger et al, 2015;Merlis et al, 2013Merlis et al, , 2016Zhou et al, 2014;Zhou et al, 2017). The parameterized convection is made to be less intrusive, allowing explicit convection to make more contributions.…”
Section: Model and Methodsmentioning
confidence: 99%